Retrospective study of incidence/prevalence of pigmentary maculopathy and retinopathy in patients receiving pentosan polysulfate sodium - Zhong Yuan; Subusola Vaughan; Carolyn Jeffcoat; Peter Hu; Ritchie Yuson; Daniel Fife; Durga Borkar (PLoS ONE, 2025)
Purpose To evaluate prevalence and incidence rates of pigmentary maculopathy and retinopathy (PM/PR), and visual acuity (VA) changes in patients exposed to pentosan polysulfate sodium (PPS) and in patients with interstitial cystitis (IC) not exposed to PPS. Methods This is a retrospective cohort study (January 2015–March 2021) which included adult de-identified patients from the American Academy of Ophthalmology IRIS® Registry (Intelligent Research in Sight) and Komodo Health database. Three patient cohorts were identified: two PPS-exposed patient cohorts, and Non-PPS-exposed IC patient cohort. Key study outcomes included PM/PR/Any (defined based on prior literature regardless of PPS exposure) and PM/PR/PPS (further defined by an algorithm that was based on clinical notes and other protocol-prespecified criteria in PPS-exposed patients), and VA changes in each respective cohort. Results Prevalence of PM/PR/Any was relatively common in patients prior to PPS exposure (4.16%–8.43%). Incidence rate of PM/PR/PPS was uncommon in both PPS-exposed cohorts (0.13–0.15 per 100 person-years). Crude incidence rates of PM/PR/Any (based on ITT analysis) varied slightly across 3 study cohorts (2.13–2.81 and 2.38 per 100-person-years for PPS-exposed cohorts and Non-PPS-exposed IC cohort, respectively). Across all 3 study cohorts, patients with PM/PR/Any appeared to have approximately 2-fold higher proportion of 3 lines of VA worsening than those without PM/PR/Any. Conclusion Prevalence of PM/PR was common in patients prior to PPS exposure. Incidence of PM/PR/PPS that may be associated with PPS exposure was relatively uncommon. Crude incidence rates of PM/PR appeared similar across all patient cohorts regardless of PPS exposure.